2009
DOI: 10.1161/strokeaha.108.543009
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Women Have Lower Rates of Stroke, Cardiovascular Events, and Mortality After Hospitalization for Transient Ischemic Attack

Abstract: Background and Purpose-Patients with transient ischemic attack (TIA) are at increased risk for stroke, cardiovascular events, and death, yet little is known about whether these risks differ for men and women. We determined whether there are sex-based differences in these outcomes 30 days and 1 year after TIA using a national sample of elderly patients. Methods-Rates of 30-day and 1-year hospitalization for TIA (International Classification of Diseases, 9th Revision Code 435), stroke (International Classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 44 publications
(69 reference statements)
4
28
0
Order By: Relevance
“…A recent US study of patients with TIA Ͼ65 years, also using hospitalization data, reported that women were significantly less likely than men to die in the year after a TIA. 3 Our results extend this research by controlling for expected survival and demonstrating a sex difference in relative survival across all ages. Importantly, we found that significant differences between women and men in relative survival were confined to the first year after a TIA hospitalization.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A recent US study of patients with TIA Ͼ65 years, also using hospitalization data, reported that women were significantly less likely than men to die in the year after a TIA. 3 Our results extend this research by controlling for expected survival and demonstrating a sex difference in relative survival across all ages. Importantly, we found that significant differences between women and men in relative survival were confined to the first year after a TIA hospitalization.…”
Section: Discussionsupporting
confidence: 80%
“…Early stroke rates vary 1,2 and recent studies report low early stroke risk with modern urgent TIA care. [3][4][5][6] In contrast to the emphasis on early stroke risk, detailed analyses of survival after TIA, and how survival varies by age, sex, and medical history have rarely been reported. Multicenter or population-based reports suggest that between 5% and 8% of patients will die within 6 months of their TIA, 7,8 and others report 5% to 15% dying by 1 year.…”
mentioning
confidence: 99%
“…Previous studies have considered TIA as a harbinger of an impending ischemic stroke and have aimed to detect demographic, clinical, or lifestyle factors significantly associated with risk for stroke occurrence after TIA [2,3,[5][6][7]. The few studies that have reported the complete results of multivariate analysis did not use risk-adjustment to account for patient types clustering at local hospitals or used geographically biased cohorts whose sizes were approximately 1% to 3% of the current study [3,5,6,12,13].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have typically focused on a single hospital or small geographic region [2,3,5,6]. Alternatively, others have relied on broader sources such as Medicare data [7,14], which may impose significant biases due to the study population being restricted to patients over the age of 65 and generally greater morbidity. In our dataset, 35% of the TIA patients were younger than 65 and would therefore not be represented in any analysis of Medicare data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation